Pengaruh Kegiatan Ekstrakurikuler Terhadap Pembentukan Watak Kewarganegaraan Siswa Sman 7 Mataram - A, Marvianti Pua.; Lestari, Dia; Hasanah, Mauizatun; Hairunisyah, Fatun; Rahmayani, Lina; Herianto, Edy (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This study examines the effect of extracurricular activities on the formation of students' civic character using a quantitative approach and correlational research type. The purpose of this study was to determine the effect of extracurricular activities on the formation of citizenship character of students of SMAN 7 Mataram. The data used in this study came from a questionnaire/questionnaire distributed to students of SMAN 7 Mataram, which met the standards set by the researcher. The population of SMAN 7 Mataram consisted of 185 students, with 37 students being the research sample. The results showed that extracurricular activities have a positive and significant effect on the formation of students' citizenship character at SMAN 7 Mataram, which means that the more students routinely carry out extracurricular activities, the more the formation of students' citizenship character will increase. The research results of the calculation of the coefficient of determination of this study are 34.4%, which means that the student character formation variable can be explained by the extracurricular activity variable by 34.4%, while the remaining 65.6% is explained by other variables not examined in this study.